Fertile and Selectively Flirty: Women's Behavior Toward Men Changes Across the Ovulatory Cycle. (February 2014) - Cantú, Stephanie M.; Simpson, Jeffry A.; Griskevicius, Vladas; Weisberg, Yanna J.; Durante, Kristina M.; Beal, Daniel J.
Past research shows that men respond to women differently depending on where women are in their ovulatory cycle. But what leads men to treat ovulating women differently? We propose that the ovulatory cycle alters women's flirting behavior. We tested this hypothesis in an experiment in which women interacted with different types of men at different points in their cycle. Results revealed that women in the ovulatory phase reported more interest in men who had purported markers of genetic fitness as short-term mates, but not as long-term mates. Furthermore, behavioral ratings of the interactions indicated that women displayed more flirting behaviors when they were at high than at low fertility. Importantly, fertile women flirted more only when interacting with men who had genetic-fitness markers, not with other men. In summary, fertility not only alters women's behavior but does so in a context-dependent way that follows adaptive logic.